Stability of Almost Closed Operators on a Hilbert Space - Messirdi, Sanaa; Djaa, Mustapha; Messirdi, Bekkai (Sarajevo Journal of Mathematics, 2024)
We introduce the notion of almost closed linear operators acting in a Hilbert space. This class of operators contains the set of all closed linear operators and is invariant under addition, composition and limits. 2000 Mathematics Subject Classification. 47A05, 47B33